Bridging the geospatial gap: Data about space and indigenous knowledge of place. Issue 11 (19th August 2020) - Briggs, Carolyn; Burfurd, Ingrid; Duckham, Matt; Guntarik, Olivia; Kerr, Di; McMillan, Mark; San Martin Saldias, Daisy
Abstract: Indigenous knowledge of place is not well‐served by today's digital geospatial technologies, such as spatial data, maps, spatial databases, and GIS. This paper aims to identify and explore new connections between Indigenous knowledge of place and digital geospatial technologies. Our analysis is structured around three key gaps in past work: (a) the overrepresentation of digital data about space, rather than knowledge of place; (b) a lack of facility to differentiate access to knowledge and enable Indigenous data sovereignty; (c) a lack of facility to support and sustain relationships between Indigenous and non‐Indigenous peoples. The paper further identifies and explores recent research topics in the field of geographic information science (GI science) with relevance to addressing these gaps. This includes identifying new serendipitous synergies with previously unconnected research areas, such as research into location privacy, uncertainty, qualitative spatial reasoning, or distributed spatial computing. The conclusions acknowledge that our retrospective approach is unlikely to lead to radical reformulation of geospatial technologies. Nevertheless, we argue that identifying technological opportunities could offer a pragmatic pathway to more rapidly bootstrap new approaches, beyond simply technological "fixes."